Additionality of debt relief and debt forgiveness, and implications for future volumes of official assistance - Léonce Ndikumana (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
This paper examines the impact of debt forgiveness and debt relief on official development assistance. From the recipient side, the econometric analysis suggests that countries that received debt relief also received more aid compared to those that did not qualify for debt relief. From the donor side, while the data indicate a decline in aid disbursement since the early 1990s, there is no econometric evidence for any direct causal relationship between the decline in aid and debt relief/forgiveness. Nonetheless, the decline in aid raises serious concerns given that developing countries' need in external resources cannot be met by debt relief alone.
Keywords: F34; F35; O11; O19; 330; debt relief; debt forgiveness; official development aid; HIPC Initiative; crowding out; Schuldenerlass; Entwicklungshilfe; HIPC